Designing mathematics problem-solving assessment with GeoGebra Classroom: proving the instrument validity - Rosyidi, Abdul Haris; Sari, Yurizka Melia; Fardah, Dini Kinati; Masriyah, Masriyah (Journal of Education and Learning (EduLearn), 2024)
Mathematics education is looking for innovative methods to foster problem-solving skills in students. This research develops a problem-solving assessment using GeoGebra Classroom, a versatile interactive mathematics software, to revolutionize mathematics formative assessment and improve students' problem-solving skills. This study adopted the analysis, design, development, implementation, and evaluation (ADDIE) instructional design model stages. The design stage created a comprehensive assessment blueprint, incorporating GeoGebra Classroom functions to create interactive problem-solving tasks. Data analysis used both quantitative and qualitative approaches. Qualitative data consisted of feedback and suggestions from assessment experts, mathematicians, and GeoGebra specialists. Meanwhile, quantitative data included expert scores and cognitive tests that measured students' problem-solving abilities. A cognitive post-test was conducted to measure the progress of students' understanding while using the assessment product. The results of the content validity analysis, assessed using Aiken's V, ranged from 0.85 to 0.92, indicating a high level of validity for the problem-solving skills assessment in terms of content and construction. Some revisions were made to the design of the developed media to make it more interactive for students. These findings suggest that we can further use problem-solving questions integrated with GeoGebra Classroom to uncover the problem-solving skills of junior high school students.